Work-Family Balance - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (The Wiley-Blackwell Encyclopedia of Gender and Sexuality Studies, 2016)
The concept of work–family balance was introduced in the 1970s in the United Kingdom based on a work–leisure dichotomy, which was invented in the mid-1800s. It is usually related to the act of balancing of inter-role pressures between the work and family domains that leads to role conflict. The conflict is driven by the organizations' views of the “ideal worker” as well as gender disparities and stereotypes that ignore or discount the time spent in the unpaid work of family and community. Solutions for balance include legislation, flexible workplace arrangements, and the market care services.
Keywords: J16; J21; 300; employment; family policy; gender division of labor; social policy; labour market